HIV-1 integration landscape during latent and active infection - Cohn, Lillian (Cell, 2015)
The barrier to curing HIV-1 is thought to reside primarily in CD4(+) T cells containing silent proviruses. To characterize these latently infected cells, we studied the integration profile of HIV-1 in viremic progressors, individuals receiving antiretroviral therapy, and viremic controllers. Clonally expanded T cells represented the majority of all integrations and increased during therapy. However, none of the 75 expanded T cell clones assayed contained intact virus. In contrast, the cells bearing single integration events decreased in frequency over time on therapy, and the surviving cells were enriched for HIV-1 integration in silent regions of the genome. Finally, there was a strong preference for integration into, or in close proximity to Alu repeats, which were also enriched in local hotspots for integration. The data indicate that dividing clonally expanded T cells contain defective proviruses, and that the replication competent reservoir is primarily found in CD4(+) T cells that remain relatively quiescent.